Faktor yang Mempengarui Kinerja Karyawan Pusat Belanja Sumber Murah Magetan - Prihayatni, Enfila; Rizal, Fitra (CV. Civiliza Publishing, 2024)
Introduction/Main Objectives: This research aims to determine the influence of Islamic Compensation and Work Environment on the performance of Employees at the Sumber Murah Magetan Shopping Center partially and simultaneously. Research Methods: The method used in this research is quantitative, with data collection techniques in the form of distributing questionnaires to 50 employees of Sumber Murah Magetan. The instrument testing techniques in this research are the classical assumption test and multiple regression analysis, including the coefficient of determination test, t-test, f-test. Finding/Results: This research shows that (1) work discipline partially has a positive and significant effect on employee performance. (2) Islamic compensation partially positively and significantly affects employee performance. (3) the work environment partially has a positive and insignificant effect on employee performance. Conclusion:To improve the quality of employee performance, Sumber Murah can focus on increasing employee discipline and job satisfaction and creating a more comfortable work environment to achieve optimal performance results.